2020
DOI: 10.14419/ijag.v8i2.31043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seismic attributes for reservoir characterization over Edi field, Niger delta, Nigeria using 3d seismic data

Abstract: Seismic attributes were evaluated over Edi field, offshore Western Niger Delta, Nigeria, via 3D seismic data. Manual mappings of the horizons and faults on the in-lines and cross-lines of the seismic sections were done. Various attributes were calculated and out put on four horizons corresponding to the well markers at different formations within the well were identified. The four horizons identified, which includes: H1, H2, H3 and H4 were mapped and interpreted across the field. The operational agenda was thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The second cycle began during the Eocene era with the emergence of the Niger Delta and is still ongoing. However, in the late Quaternary, uplift and erosion frequently interrupted sedimentation, resulting in submerged canyons formed by cycles of channel cutting and filling [12,14].…”
Section: Methods Study Area Geologymentioning
confidence: 99%
“…The second cycle began during the Eocene era with the emergence of the Niger Delta and is still ongoing. However, in the late Quaternary, uplift and erosion frequently interrupted sedimentation, resulting in submerged canyons formed by cycles of channel cutting and filling [12,14].…”
Section: Methods Study Area Geologymentioning
confidence: 99%
“…To identify gas directly on seismic recordings, a more reliable indicator than bright spots on stacked sections is required [4] . Li (2021) demonstrated that gas-sand reflection coefficients exhibit unique behavior with increasing offset, serving as a direct hydrocarbon indicator on seismic data [5] .…”
Section: Introductionmentioning
confidence: 99%